2015
DOI: 10.3390/nu7085272
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Supplementation with a Vitamin and Mineral Complex with Guaraná Prior to Fasted Exercise on Affect, Exertion, Cognitive Performance, and Substrate Metabolism: A Randomized Controlled Trial

Abstract: Exercise undertaken in a fasted state can lead to higher post-exercise mental fatigue. The administration of a vitamin and mineral complex with guaraná (MVM + G) has been shown to attenuate mental fatigue and improve performance during cognitively demanding tasks. This placebo-controlled, double-blind, randomized, balanced cross-over study examined the effect of MVM + G consumed prior to morning exercise on cognitive performance, affect, exertion, and substrate metabolism. Forty active males (age 21.4 ± 3.0 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 57 publications
(82 reference statements)
4
39
2
1
Order By: Relevance
“…Up to the present time, very few studies have investigated the interaction effect of GUAc ingestion and exercise on cognitive function. In a recent study, Veasey et al 9 highlighted an increase in accuracy of numeric working memory and in speed of picture recognition after exercise when compared to PL. Even if mechanisms explaining guarana effects remain unclear, taken together, these results suggest that GUAc ingestion could be an interesting nutritional strategy to enhance cognitive functioning even if effects on response inhibition at the end of exercise remains limited.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Up to the present time, very few studies have investigated the interaction effect of GUAc ingestion and exercise on cognitive function. In a recent study, Veasey et al 9 highlighted an increase in accuracy of numeric working memory and in speed of picture recognition after exercise when compared to PL. Even if mechanisms explaining guarana effects remain unclear, taken together, these results suggest that GUAc ingestion could be an interesting nutritional strategy to enhance cognitive functioning even if effects on response inhibition at the end of exercise remains limited.…”
Section: Discussionmentioning
confidence: 98%
“…reported to enhance cognitive functioning at rest 7,8 and during exercise 9 , possibly due to a number of potential stimulants such as caffeine, flavonoids, saponins or tannins 10,11 .…”
Section: Guarana Ingestion Has Beenmentioning
confidence: 99%
“…Both MVM + G studies measured attention using RVIP. While Kennedy et al [60] found an improvement in RVIP speed and accuracy, Veasey et al [61] did not, nor on choice reaction time. Kennedy et al [59] also found mixed results from pure guarana extract supplementation: speed, but not accuracy, of attention was enhanced by guarana.…”
Section: Guarana and Multivitaminsmentioning
confidence: 90%
“…Four studies, involving a total of 224 participants, examined the effect of acute doses of guarana on cognition (see Table 3). Two utilised crossover designs [59,61] and two used an independent groups design [58,61]. Sample compositions varied across the studies: predominantly female (two studies), approximate even gender distribution (one study), and active males only (one study).…”
Section: Guarana and Multivitaminsmentioning
confidence: 99%
See 1 more Smart Citation